The Forest Sisters: Women in the Estonian Post-World War II Forest Brother Movement - Kaasik, Peeter (Genocidas ir rezistencija, 2024)
In historical tradition, the ‘forest brother movement’ means going into hiding in the woods, bogs, or on bog islands to escape wars or looting raids. The term ‘forest brother’ came into use as a more contemporary general term during the German occupation (1941–1944). It originally meant the brotherhood in arms of the time of the Summer War of 1941 but its meaning quickly started broadening. Although forest brothers are even nowadays defined as participants in armed resistance, generally speaking, in historical literature, everyone who hid themselves from the Soviet regime is referred to using this term, regardless of age and gender.While ‘the forest brother movement’ and ‘forest brother’ are established general terms, ‘forest sister’ is more of a colloquial expression. Thus, that term has not gained general acceptance in historical literature. Although as a rule, the gender of forest brothers is abstract in research papers, the term itself can lead to the mistaken understanding that only men hid themselves or fought against the Soviet regime. For that reason, this overview attempts to fill that gap and shed some light on the role of women in the history of the forest brother movement after the Second World War.
Keywords: Forest sisters; Deportation; Resistance; Concealment; Forest brothers